Recent Developments in Materials and Manufacturing Techniques Used for Sports Textiles. (22nd February 2023) - Ahmad, Faheem; Akhtar, Khurram Shehzad; Anam, Wardah; Mushtaq, Bushra; Rasheed, Abher; Ahmad, Sheraz; Azam, Farooq; Nawab, Yasir
Abstract : In the recent era of development, the global market for the sportswear textile manufacturing industries has increased with the increase in consumption of active sportswear. The sportswear manufacturers not only focused on the market trends but also focused on material diversification with technology enhancement. The performance characteristics of active sportswear directly influence comfort level and athletic performance during sports activities. Different types of sportswear products require different performance characteristics. Appropriate moisture and heat management are the key factors for the endowment of the required physiological comfort level. In highly engineered textile-based sports goods, special characteristics are incorporated in the polymer/fibers/product manufacturing procedures/finishing techniques to obtain the maximum performance and comfort level. In this review paper current market trends, highly engineered polymers, fibers, fabrics, finishes, nanomaterials, and the recent developments in the manufacturing techniques of sportswear are illustrated.